Combined steam and CO2 reforming of methane for syngas production over carbon-resistant boron-promoted Ni/SBA-15 catalysts - Tan, Ji Siang; Pham, Thong L. M.; Cuong, Nguyen Van; Phuong, Pham T. T.; Phuc, Nguyen Huu Huy; Truong, Quang Duc; Vo, Dai-Viet N. (Elsevier Ltd, 2018)
The unpromoted and B-promoted 10%Ni/SBA-15 catalysts synthesized via sequential incipient wetness impregnation approach were assessed for combined steam and CO2 reforming of methane (CSCRM) at various reaction temperatures of 973–1073 K and stoichiometric feed composition. An expected and noteworthy drop in mean NiO crystallite size and BET surface area with boron promotion from 1% to 5%B loading could be due to the agglomeration of B2O3 particles and deboration reaction during calcination and hence blocking mesopores of SBA-15 support at elevated B composition. The complete NiO reduction to metallic Ni0 form was achieved during H2 activation and the reduction temperature of NiO phase was shifted towards higher temperature with B-addition owing to enhancing interaction between the acidic B2O3 and basic NiO phases. For all reaction temperature employed, 3%B appeared to be the optimal promoter loading in terms of reactant conversions and 3%B-10%Ni/SBA-15 catalyst revealed the greatest H2 yield (69.4%) at 1073 K. In addition, CH4 and CO2 conversions were enhanced about 23.2% and 32.4%, correspondingly with rising reaction temperature from 973 to 1073 K. Ratio of H2 to CO varied from 1.26 to 2.71 and the desired H2/CO ratio of about 2 favored for Fischer-Tropsch synthesis was achieved on 3%B-10%Ni/SBA-15 sample at 973 K. Boron promoter suppressed graphitic carbon formation and the amount of carbonaceous deposition was reduced about 4 times. Noticeably, 3%B-10%Ni/SBA-15 was also resilient to metallic Ni0 re-oxidation throughout CSCRM.